2022
DOI: 10.3389/fpsyg.2021.778312
|View full text |Cite
|
Sign up to set email alerts
|

Paranormal Experience Profiles and Their Association With Variations in Executive Functions: A Latent Profile Analysis

Abstract: This study investigated relationships between inter-class variations in paranormal experience and executive functions. A sample of 516 adults completed self-report measures assessing personal encounter-based paranormal occurrences (i.e., Experience, Practitioner Visiting, and Ability), executive functions (i.e., General Executive Function, Working and Everyday Memory, and Decision Making) together with Emotion Regulation and Belief in the Paranormal. Paranormal belief served as a measure of convergent validity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 70 publications
1
10
0
Order By: Relevance
“…The observation that belief in the paranormal interacts with cognitive-perceptual personality factors in complex ways (Navarro and Guerra, 2020), which are differentially related to outcome measures such as well-being, concurs with recent studies using latent profile analysis (see Denovan et al, 2018;Drinkwater et al, 2022a). This emerging research designates that consideration of discrete, self-ascribed paranormal attributes (i.e., belief, experience, and ability) and cognitive-perceptual factors in isolation (i.e., schizotypy and transliminality) is too simplistic.…”
Section: Moderation Analysissupporting
confidence: 83%
See 1 more Smart Citation
“…The observation that belief in the paranormal interacts with cognitive-perceptual personality factors in complex ways (Navarro and Guerra, 2020), which are differentially related to outcome measures such as well-being, concurs with recent studies using latent profile analysis (see Denovan et al, 2018;Drinkwater et al, 2022a). This emerging research designates that consideration of discrete, self-ascribed paranormal attributes (i.e., belief, experience, and ability) and cognitive-perceptual factors in isolation (i.e., schizotypy and transliminality) is too simplistic.…”
Section: Moderation Analysissupporting
confidence: 83%
“…The potential psychological benefits of paranormal advocacy are not merely limited to belief and experience. In a recent study using reflexive thematic analysis, Drinkwater et al (2022a , b) found that justification of professed paranormal abilities created a sense of personal coherence and significance by providing a framework for structuring significant life events.…”
Section: Introductionmentioning
confidence: 99%
“…The computation of model fit statistics ensures that class enumeration is less arbitrary (Terhune and Cardeña, 2010;Flensborg Damholdt et al, 2012). Acknowledging this, investigators have recently employed LPA (see Denovan et al, 2018;Drinkwater et al, 2021Drinkwater et al, , 2022.…”
Section: The Present Studymentioning
confidence: 99%
“…Guest et al (2006) , following iterative assessment of coding, concluded that a sample size of 12 is frequently acceptable for interview studies exploring common experiences in a relatively homogeneous sample. Although, incidence of ability is under researched and therefore difficult to ascertain, recent research by Drinkwater et al (2021a , b , c , 2022) designated that a significant percentage of respondents admit self-ascribed paranormal abilities. In the case of the Drinkwater et al (2021a , c) studies, the sample sizes were relatively large ( n = 917 and n = 499, respectively) and indicated that professed ability was relatively common.…”
Section: Discussionmentioning
confidence: 99%
“…Although, researchers have historically focused on supernatural “beliefs” and “experiences” rather than ability (e.g., Dagnall et al, 2016 ; Drinkwater et al, 2020 ), this topic is important for several reasons. Theoretically it is necessary since the psychology of ability is relatively under researched compared to belief and experience ( Drinkwater et al, 2021a , c , 2022 ), Thus, investigation of self-ascribed capabilities extends conceptual understanding of paranormal attributions. Explicitly, it provides insights into complex interactions between credence and direct participation.…”
Section: Introductionmentioning
confidence: 99%